Complementary and alternative medicine use in the prevention of COVID-19 pandemic: a cross-sectional survey in Kerala, India - Mini, G. K.; Grace, Chitra A.; Jinbert, Lordson (International Journal Of Community Medicine And Public Health, 2021)
Background: Globally, there is evidence of increased Complementary and alternative medicine (CAM) use during epidemics, and pandemics. Recent studies have shown that there is an increased use of CAM during the coronavirus disease (COVID-19) pandemic. The aim of the study was to investigate the pattern of CAM practice in the prevention of COVID-19 pandemic among adults in Kerala state, India. Methods: This was a cross-sectional descriptive study conducted in the first week of June 2021 among adults residing in Kerala state. The study used a pre-tested google form to collect the data. A total of 548 individuals aged 18-84 years answered an online questionnaire for the present study. Results: A higher proportion (52.4%) of participants were aged <30 years, 30.8% were males, 55.3% rural residents, 26.6% health care professionals, and 51.1% had a regular income. CAM use prevalence was 59.3% (95% CI: 55.1 to 63.3). Social media (46.9%) was the most frequently reported source of CAM. The age-adjusted analysis results showed that CAM use was higher among health professionals (OR: 2.15, 95% CI: 1.41-3.27), those who did not believe that vaccine could prevent coronavirus (OR: 1.91 CI: 1.08-3.39), and those who were having no regular income (OR: 1.56, CI: 1.04-2.34), compared to their counterparts. Conclusions: Close to 60% of CAM use in this population is a public health concern since the efficacy of CAM use for the prevention or treatment of COVID-19 is not known. The CAM users will be under a sense of false protection, which is likely to negate vaccination and seeking proper treatment for COVID -19 in Kerala.